Skin dose for head and neck cancer patients treated with intensity-modulated radiation therapy(IMRT). (November 2017) - Fu, Hsiao-Ju; Li, Chi-Wei; Tsai, Wei-Ta; Chang, Chih-Chia; Tsang, Yuk-Wah
Abstract: The reliability of thermoluminescent dosimeters (ultrathin TLD) and ISP Gafchromic EBT2 film to measure the surface dose in phantom and the skin dose in head-and-neck patients treated with intensity-modulated radiation therapy technique(IMRT) is the research focus. Seven-field treatment plans with prescribed dose of 180 cGy were performed on Eclipse treatment planning system which utilized pencil beam calculation algorithm(PBC). In calibration tests, the variance coefficient of the ultrathin TLDs were within 3%. The points on the calibration curve of the Gafchromic film was within 1% variation. Five measurements were taken on phantom using ultrathin TLD and EBT2 film respectively. The measured mean surface doses between ultrathin TLD or EBT2 film were within 5% deviation. Skin doses of 6 patients were measured for initial 5 fractions and the mean dose per-fraction was calculated. If the extrapolated doses for 30 fractions were below 4000 cGy, the skin reaction grading observed according to Radiation Therapy Oncology Group (RTOG) was either grade 1 or grade 2. If surface dose exceeded 5000 cGy in 32 fractions, then grade 3 skin reactions were observed. Highlights: Using ultrathin TLD and EBT films to measure skin dose. Both the EBT films and ultrathin TLDs exhibited a deviation within 5%. The Dp curve and distances between surfaces can be used to assess surface dose. About 5000 cGy delivered within 32 days result in Grade 3 skin reaction.